Rescue right ventricular outflow tract stenting for refractory hypoxic spells. Issue 2 (13th December 2022) - Sasikumar, Navaneetha; Mohanty, Satish; Balaji, Seshadri; Kumar, Raman Krishna
Abstract: Background: While right ventricular outflow tract stenting (RVOTS) has become an acceptable alternative to palliative surgery in Tetralogy of Fallot (TOF) and similar physiologies, its utility for relief of refractory hypoxic spells is unclear. Methods: Patients who underwent RVOTS for emergency relief of refractory hypoxic spells were identified. Specific modifications to enable expeditious RVOTS included use of stent delivery systems (guiding catheter or long sheath) upfront to minimize catheter exchanges; using coronary wires to cross RVOT initially; stabilizing the catheter with a wire in the aorta while crossing RVOT with a second wire. Results: From 2015 to 2022, 11 patients underwent RVOTS for hypoxic spells refractory to medical management. Their median age was 27 days (IQR 8.5–442.5); weight 3.27 kg (2.7–8.96); 9 males. Median pulmonary annulus Z score was −4.13 (IQR−4.85 to −0.86). Thirteen stents with median diameter 5 (4–6.5) mm and length 19 (16–19.75) mm were implanted, fluoroscopy time:13.6 (11–26.3) min; procedure time (60, 30–70 min). All were ventilated. Oxygen saturations improved from 45% (40–60) to 90% (84–92); ( p  < 0.0001) with no major complications. Postprocedure ventilation was needed for 21 (20–49) hours and 4 required diuretic infusion for pulmonary over‐circulation. Four needed re‐stenting 13 days to 5 months later. At median follow‐up of 7 (4–17) months; 2 died from unrelated causes, 3 underwent surgery (two correction and one aorto‐pulmonary shunt) and 6 await surgery. Conclusion: RVOTS enables safe, expeditious and effective short‐term palliation for refractory hypoxic spells. Specific technical modifications facilitate safety, ease and swiftness.